The star of kazan - Ibbotson, Eva (Macmillan Children's Books London, 2005)
Set mainly in Vienna in the early 1900s, where foundling Annika has been taken in to an eccentric and warmhearted household. After she inherits a trunk of costume jewelry, a woman claiming to be her aristocratic mother arrives and takes her to live in a strangely decrepit mansion in Germany. Warm, quirky and funny. 9 yrs+